Work Commitment, Work Discipline, and Competence Effects on Teacher Performance: Evidence from an Islamic Private School in Medan - Sahat Simbolon (Jurnal Studi Multidisiplin Ilmu, 2024)
Purpose: This study investigates the partial and simultaneous effects of work commitment, work discipline, and competence on teacher performance at Sekolah Guang Ming Medan, a private educational institution in North Sumatra, Indonesia, where suboptimal teacher performance has been observed in commitment consistency, disciplinary adherence, and professional competency alignment.Methodology: A quantitative survey design was employed. The study population comprised all 53 permanent teachers at the school, and a census sampling technique enrolled all 53 individuals as respondents. Data were collected through structured Likert-scale questionnaires. Instrument validity was assessed using Pearson correlation and reliability via Cronbach's alpha. Classical assumption tests and multiple linear regression analyses were conducted using IBM SPSS Statistics version 20.0.Results: All instruments were valid and highly reliable. Work commitment (t = 2.285, p = .003), work discipline (t = 1.850, p = .000), and competence (t = 1.760, p = .004) each exerted positive and significant partial effects on teacher performance. The simultaneous F-test confirmed joint significance (F = 175.34, p = .000), with the three predictors jointly explaining 81.2% of the variance in teacher performance (Adjusted R² = 0.812). Conclusions: Competence produced the largest marginal performance gain (B = 0.213), followed by work discipline (B = 0.161) and work commitment (B = 0.048).Limitations: The single-school census design restricts generalizability, and the cross-sectional approach limits causal inference.Contributions: This study provides the first integrated threepredictor quantitative analysis of teacher performance determinants at Sekolah Guang Ming Medan, offering evidencebased guidance for school human resource management.